Efektivitas Absensi Berbasis Teknologi Fingerprint Dalam Upaya Peningkatan Kinerja Aparatur Desa Tanah Towa - Andi Ahmad malikul Afdal; Muh. Faisal (Ikatan Ahli Informatika Indonesia, 2023)
This research contains field research that examines the effectiveness of attendance based on fingerprint technology in efforts to improve the performance of Tanah Towa village officials. This research aims to examine the fingerprint electronic attendance process in improving the performance of Tanah Towa village officials and the effectiveness of technology-based attendance in efforts to improve the performance of Tanah Towa village officials. In this research the author uses a qualitative approach, using research strategies and techniques to understand society by collecting as many in-depth facts as possible, the data is presented in verbal form. The conclusion of this research proves that the existence of electronic-based attendance used by Tanah Towa village really helps improve the performance of Tanah Towa village officials, although in the implementation process there are obstacles, but with the passage of time and commitment to efforts to improve the performance of the Tanah Towa village head these obstacles can be achieved. resolved well.